THE PRESCHOOL TEACHERS’ PROFESSIONAL GROWTH BY MEANS OF USING THE TECHNOLOGY OF ARTIFICIAL INTELLIGENCE - Будилко, Ю.Е.; Швец, Н.А. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The relevance of the topic under study can be defined as due to the gap between the level of information and communication skills of modern teachers and children, starting from preschool age. The authors show the possibility of using artificial intelligence technology in the form of various applications in working with older preschool children. They also present this technology as an effective means of teachers’ professional growth.
Keywords: digitalization; preschool education; teacher; professional growth; artificial intelligence